PREDIKSI KEBUTUHAN TENAGA PENDIDIK BERDASARKAN PERTUMBUHAN JUMLAH SISWA/I MENGGUNAKAN METOE MONTE CARLO - Hasibuan, Cici Cahyati; Wanayumini, Wanayumini (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to predict the need for educators at the junior high school level in Asahan Regency based on student growth using the Monte Carlo method. This process is done by generating random numbers through the Linear Congruential Method (LCM) and mapping them into the probability distribution of the number of students based on historical data. The prediction results show the number of junior high school students in 2026 reached 41,161 people. Based on the ideal ratio of 1 teacher for 20 students, an additional 785 educators are needed in sub-districts that experience shortages. This prediction system is developed in the form of a web-based application using PHP and MySQL to support the automatic simulation process. The implementation of this system is expected to help the Education Office in planning educators' needs efficiently and data-based. Keyword: Prediction; Monte Carlo; Educators; Students. Abstrak: Penelitian ini bertujuan untuk memprediksi kebutuhan tenaga pendidik tingkat SMP di Kabupaten Asahan berdasarkan pertumbuhan jumlah siswa menggunakan metode Monte Carlo. Proses ini dilakukan dengan membangkitkan angka acak melalui metode Linear Congruential Method (LCM) dan memetakannya ke dalam distribusi probabilitas jumlah siswa berdasarkan data historis. Hasil prediksi menunjukkan jumlah siswa SMP pada tahun 2026 mencapai 41.161 orang. Berdasarkan rasio ideal 1 guru untuk 20 siswa, dibutuhkan tambahan sebanyak 785 tenaga pendidik di kecamatan yang mengalami kekurangan. Sistem prediksi ini dikembangkan dalam bentuk aplikasi berbasis web menggunakan PHP dan MySQL untuk mendukung proses simulasi secara otomatis. Implementasi sistem ini diharapkan dapat membantu Dinas Pendidikan dalam merencanakan kebutuhan tenaga pendidik secara efisien dan berbasis data. Kata kunci: Prediksi; Monte Carlo; Tenaga Pendidik; Siswa.